Hubungan Karakteristik Ibu Yang Memiliki Anak Balita Stunting Dengan Tingkat Kecemasan Di Wilayah Kerja Puskesmas Kesesi I Kabapaten Pekalongan - nabila, inas; Nurlaela, Emi (PENA NURSING, 2024)
The problem of stunting has an impact on short-term and long-term health and functional consequences in the future, causing most parents, especially mothers, to experience anxiety. This study aims to determine the relationship between the characteristics of mothers who have stunted toddlers with anxiety levels. This research is a quantitative research with a descriptive correlation research design. The approach used is cross sectional. Samples were selected using total sampling technique. The sample in this study was mothers who had stunted children under five in the Work Area of the Health Center Kesesi I Pekalongan Regency, totaling 77 respondent. The research instrument used was a questionnaire. The results showed that the characteristics of the respondents consisted of 52 respondents (67.5%) aged 20-35 years, 52 respondent's children (67.5%) aged 36-59 months, 26 respondents (33.8%) educated SMP/MTS, 48 respondents (62.3%) did not work, 57 respondents (74%) had multipara parity, 75 respondents (97.4%) had a number of children who experienced stunting 1 child, 60 respondents (77.9%) had the impact of stunting neither of them bothered and 41 respondents (53.2%) felt anxious. The results of the Chi square test showed that mother's age, education, parity had a significant relationship with the anxiety level of mothers who had stunted toddlers, while the child's age, occupation, number of children who were stunted, and the impact of stunting experienced had no significant relationship with the anxiety level of mothers who had stunted toddlers.